Hydrocortisone granules in capsules for opening (Alkindi) as replacement therapy in pediatric patients with adrenal insufficiency. (4th March 2021) - Coope, Helen; Parviainen, Lotta; Withe, Mike; Porter, John; Ross, Richard J
ABSTRACT: Introduction: Treatment of pediatric adrenal insufficiency (AI) has been challenging due to a lack of dose and age appropriate hydrocortisone preparations for children. Hydrocortisone granules in capsules for opening (Alkindi) is the only licensed replacement therapy specifically designed for use in pediatric adrenal insufficiency. Areas Covered: The high unmet need of the pediatric AI patient population for a licensed, dose-appropriate hydrocortisone formulation and the development and approval of hydrocortisone granules in capsules for opening for pediatric AI. Expert opinion: To date, treatment of children with AI has relied on parents or pharmacists crushing tablets of hydrocortisone. Pediatric patients have suffered from over- and under-treatment with poor health outcomes. Hydrocortisone granules in capsules for opening provides accurate, age-appropriate dosing, allowing appropriate dose titration for the growing child. The granule-based formulation is taste masked to hide the bitterness of hydrocortisone, and in clinical trials was well tolerated and easily administered to children. The granules can be administered either directly to the mouth or sprinkled onto soft food or yogurt. Hydrocortisone granules in capsules for opening provides the first licensed treatment option specifically designed for pediatric patients with AI.